2014
DOI: 10.5534/wjmh.2014.32.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Testicular Biopsy Histopathology as an Indicator of Successful Restoration of Spermatogenesis after Varicocelectomy in Non-obstructive Azoospermia

Abstract: PurposeWe aimed to evaluate the efficacy of using testicular biopsy histopathology as an indicator of the success of loupe-assisted subinguinal varicocelectomy in non-obstructive azoospermia (NOA) patients.Materials and MethodsIn a 2-year period, a prospective study was carried at Minoufiya University Hospital on 20 NOA patients with clinical bilateral varicoceles. These patients underwent loupe-assisted subinguinal varicocelectomy with simultaneous testicular biopsy. All patients were evaluated by determining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 21 publications
4
31
0
Order By: Relevance
“…However, our systematic review included three further studies, and analysis was limited to the motile sperm in ejaculate to determine successful outcome of varicocele repair. These three studies showed that varicocele repair improved sperm count in non-obstructive azoospermic men [3,14,15]. Hypospermatogenesis and late maturation arrest pattern were associated with an optimal outcome of varicocele repair.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, our systematic review included three further studies, and analysis was limited to the motile sperm in ejaculate to determine successful outcome of varicocele repair. These three studies showed that varicocele repair improved sperm count in non-obstructive azoospermic men [3,14,15]. Hypospermatogenesis and late maturation arrest pattern were associated with an optimal outcome of varicocele repair.…”
Section: Resultsmentioning
confidence: 99%
“…Open testicular biopsy was carried out on healthier testis based on size or consistency before or at the same time of varicocele repair. However, only two studies mentioned that varicocele repair and open testicular biopsy were performed by one surgeon only or together with a team [6,15]. This may result in differing opinions regarding the performance.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations